Understanding differences in essay writing experience and essay texts amongst a group of higher education students identified as dyslexic: a view of dyslexia in context - Carter, Christine (2014)
This study applies socio-cultural theories to explore how differences in essay writing experience and essay texts are constituted for a group of students identified as dyslexic. It is a qualitative study with eleven student writers, seven of whom are formally identified as dyslexic, from the schools of archaeology, history and philosophy in a pre-1992 UK university. Semi-structured interviews before, during and after writing a coursework essay revealed well-documented dyslexia-related difficulties, but also strong differences in how writing was experienced. The multiple and fluid dimensions that construct these differences suggest the importance of position within the context, previous and developing writing and learning experience and meta-affective, meta-linguistic and metacognitive awareness. Close analysis of how essays evolved and of samples of 'difficult' texts reveal the multiple ways that communication can be compromised. This suggests that much more nuanced descriptions are needed of essay writing in this group. Findings from the interview data and essay texts further suggest tensions between specialist and inclusive writing pedagogy for students identified as dyslexic.